Chrysophyllum cainito: A Tropical Fruit with Multiple Health Benefits. (19th February 2020) - Doan, Hau V.; Le, Thao P.
Abstract : Chrysophyllum cainito is a tropical fruit tree with multiple benefits to human health. C. cainito possesses strong antioxidant properties either in vitro or in vivo . Extracts from the leaves, stem bark, fruits, peel, pulp, or seed of C. cainito are promising candidates in traditional medicine for curing diabetes and fighting against bacterial, fungal, and viral infections. C. cainito leaf extract alone or in a complex formula exhibits anti-inflammatory responses by reducing hypersensitivity, acts as inflammatory markers, and has antinociceptive effects. The leaf extract also increases wound healing speed and assists in regulating fat uptake. In addition, the C. cainito fruit shows anticancer activity against osteosarcoma. In conclusion, the aerial parts of C. cainito have strong beneficial biological effects on human health.